Infection of ixodes ticks and wild small mammals with pathogens of natural focal infections in the territory of the Kurortny district of St. Petersburg - D. I. Grechishkina; I. A. Karmokov; R. R. Baimova; E. G. Riabiko; E. S. Khalilov; I. S. Lyzenko; A. A. Sharova; G. A. Lunina; O. A. Freylikhman; N. K. Tokarevich (Журнал инфектологии, 2025)
The purpose of this study was to identify the genetic markers of Borrelia burgdorferi sensu lato, Rickettsia spp. SFG, Anaplasma phagocytophilum, Ehrlichia caffeensis/E. muris, Coxiella burnetii, and tick-borne encephalitis virus (TBE) in ixodes ticks and organs of wild small mammals collected and captured in 2020-2023 in the Kurortny district of St. Petersburg.Materials and methods. Samples of ixodes ticks and organs of wild small mammals were examined by real-time PCR for the presence of genetic material of the causative agents of tick-borne infections. Ixodes ticks were collected and wild small mammals were captured in the Kurortny district of St.Petersburg in the period 2020-2023. The study was conducted using commercial test systems.Results. The overall infection rates of ixodes ticks and wild small mammals in relation to B. burgdorferi s.l. were 23.7% and 5.2%, respectively; Rickettsia spp. SFG – 11.5% and 0.9%; E. chaffensis/ E. muris – 4.0% and 0.0%; A. phagocytophilum – 1.6% and 0.6%; C. burnetii – 3.3% and 5.2%; tick–borne encephalitis virus – 0.2% and 0.0%. The total infection rate of ticks with two or more pathogens was 6.6%, the most common combinations of mixed infections were: B. burgdorferi s.l. + Rickettsia spp. SFG, B. burgdorferi s.l. + C. burnetii and B. burgdorferi s.l. + E. chaffensis/ E. muris.Conclusion. The results obtained indicate the existence of active natural foci of tick-borne infections in the Kurortny district of St. Petersburg and substantiate the expediency of continuous entomological and zoological monitoring and improvement of preventive measures against tick-borne infections.